Teaching English to Young Learners Through Songs - Setyaningsih, Ani (English Education Department, Universitas Islam Indonesia, 2007)
Globalisation brings a great impact on the use of English in any domains like business, education, IT and the like. English has become lingua franca one chooses to communicate with others having a different language. English has spread worldwide and this phenomenon has resulted in English teaching learning in primary level in many non- English-speaking countries. This brings a consequence to a crucial need in teachers' education. Teachers at the primary level need to develop both competence in English use and teaching skills to young learners regarding their special characteristics. Theories in children development is needed by teachers to meet the special needs of children. One method suggested to meet those needs through songs